Economic impact of pharmacists' interventions in asthma management: a systematic review - Gabriel R. FREITAS; Juliana U. SANTOS; Juliana S. FRANÇA; Rodrigo S. PINTO; Brayan V. SEIXAS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: The purpose of this study was to review in a systematically way the studies that investigated the economic impact of clinical pharmacist services delivered to asthma individuals. Methods: A systematic survey was conducted in the PubMed, Scopus, Lilacs and Cochrane databases aiming to grade the economic evaluations published until January 2020. English, Spanish, Portuguese or French language articles were included if they evaluated a pharmaceutical intervention aiming asthma patients and also reported economic data about these interventions. There was no limitation regarding the study design or type of economic analysis. Two independent authors assessed and selected the studies, extracted the data, and measured risk of bias. Risk of bias was measured through the Cochrane's risk of bias tool for randomized controlled trials and the Newcastle-Ottawa quality assessment scale for cohort studies. Results: 2,832 references were identified through the search strategy, but only seven studies met the inclusion criteria to be selected into the final analysis. Out of these seven articles, four consisted of cohort studies, and three consisted of randomized controlled trials. Instructional programs and patient counseling were the most usual components of pharmaceutical care interventions. Six articles showed statistically significant positive economic outcomes of pharmaceutical care interventions in asthma management. Moreover, pharmaceutical interventions were found to decrease hospitalizations, emergency visits, symptoms, and increase adherence to pharmacotherapy. Conclusions: Studies included showed acceptable and satisfactory cost-saving ratios, demonstrating the potential benefit of inserting the pharmacist into the multidisciplinary team. Nevertheless, long-term studies and randomized clinical trials are needed to establish solid evidence in order to expand the results found in this review to broader and different contexts.